Non-metastatic primary neuroendocrine neoplasms of the breast: a reference cancer center’s experience of a heterogenous entity - Püsküllüoğlu, Mirosława; Grela-Wojewoda, Aleksandra; Ambicka, Aleksandra; Pacholczak-Madej, Renata; Pietruszka, Agnieszka; Mucha-Małecka, Anna; Rudzińska, Agnieszka; Ziobro, Marek; Ryś, Janusz; Mituś, Jerzy W. (Frontiers in Endocrinology, 2024)
Background: Primary neuroendocrine neoplasms of the breast (Br-NENs) are rare. The classification has been updated in recent years making interpretation of the data published challenging. It is unclear whether neuroendocrine differentiation is associated with poorer prognosis and what treatment approaches should be applied. Methods: The database for breast cancer patients treated between 2009 and 2022 at the Maria Sklodowska-Curie National Research Institute of Oncology Branch Krakow was explored to search for Br-NENs. Patients’ medical and pathological data were collected and analyzed. Results: We included 22 females with Br-NEN without metastases at the time of diagnosis. The median age was 64 years (range: 28-88), Of the cases, 18 were hormone receptor positive, all were HER-2 negative, the median Ki67 was 27% (10-100%). The median tumor size at the time of diagnosis was 29.5mm (7-75mm), 9 patients were N-positive. DCIS was present in 5 cases. Only one case was negative for chromogranin and synaptophysin staining, but data were missing for 4 cases. Nine patients received adjuvant chemotherapy, mainly based on anthracyclines and taxanes, while 16 received adjuvant hormonal therapy and 15 received postoperative radiotherapy. Radical surgery was performed in all patients, but two underwent suboptimal tumorectomy. One patient had local recurrence, three experienced metastatic disease, all involving the lungs, but these patients are still alive. The median follow-up was 96 months (8-153). Two patients died, with a follow up time of no recurrence >4 years. Our results were compared to twelve case series collecting clinical data on Br-NENs, with median patient number of 10.5 (range: 3-142). Conclusion: Br-NENs represent a heterogenous group of diseases, lacking data from prospective studies or clinical trials. There are no established treatment standards tailored for Br-NENs. Our patients’ cohort exhibited a favorable prognosis, potentially attributed to lower tumor stage and Ki67 index compared to other reported case series. We suggest that radical surgery and postoperative radiotherapy be administered akin to standard treatment for breast cancer of no special type. ESMO also advocates for this approach in systemic treatment, although we recommend considering platinum-based chemotherapy for patients with poorly differentiated Br-NENs exhibiting high Ki67.